KEBIJAKAN PEMBANGUNAN PADA DAERAH TANGKAPAN AIR PLTA KOTO PANJANG, KABUPATEN LIMAPULUH KOTA - iswandi umar; Indang Dewata (Universitas Negeri Padang, 2020)
The population increases every year, as a result of increasing land demand for life activities. Changes in forest land to other uses, have an impact on the sustainability of the water system and river flow. This will have an impact on the sustainability of PLTA Koto Panjang. This study aims to determine the direction of energy sustainability policy of electricity in water catchment area Koto Panjang. To see land use change using Landsat ETM 7 2005 image, and Landsat imagery of Oli 8 years 2018. The method used to determine the direction of Koto Panjang hydropower energy sustainability policy using ISM analysis, in this analysis involving experts as much as 20. The results of land use analysis of about 70 percent of the catchment area changed from primary forest to secondary forest. Direction of energy sustainability policy on PLTA Koto Panjang, it is necessary to increase the cooperation between responsible institutions and law enforcement on the environment.